The Implementation of Instagram in Mobile-assisted Language Learning for EFL students: A Gender-Based Analysis - Hardianti Hardianti; Arqam; Ambo Dalle; Magdahalena Tjaila; Abdul Haris Sunubi (Yayasan Kyadiren, 2026)
This study investigated the implementation of Instagram as a Mobile-Assisted Language Learning (MALL) tool in EFL learning and examined gender differences in students’ learning experiences. This study employed a mixed-methods design with an explanatory sequential approach. The participants were 20 tenth-grade students at MAN 1 Kota Makassar, consisting of 10 male and 10 female students. Data were collected through classroom observation, questionnaires, and semi-structured interviews. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed through data reduction, data display, and conclusion drawing. The findings showed that Instagram supported students’ reading, writing, listening, and speaking activities through captions, posts, comments, reels, videos, and speaking tasks. Female students obtained higher mean scores and showed greater participation and confidence than male students. This study concludes that Instagram can be an effective MALL tool when used through structured and inclusive EFL learning activities.